The IDENTIFIKASI CENDAWAN PATOGEN PENYEBAB BERCAK DAN HAWAR DAUN JABON PUTIH (Anthocephalus cadamba) ASAL BOGOR - Elis Nina Herliyana; Hasan Basri; Yeni Herdiyeni; Abdul Munif; Prayogo Probo Asmoro; Adisti Triani Wandayanti (Journal of Tropical Silviculture, 2026)
In Indonesia, there are two types of jabon: one of which is white jabon (Anthocephalus cadamba Roxb.). White jabon is a type of jabon that is often cultivated. The prospect of developing jabon plants that continue to increase has led to an increase in the need for jabon seedling supplies. However, the development of jabon seedlings is hampered by infections of pathogens that cause leaf diseases in white jabon seedlings in nurseries. Information related to pathogenic fungi that cause leaf spot and blight symptoms in white jabon is still not widely known. This study aims to identify pathogenic fungi that cause leaf spot and blight symptoms in White Jabon (Anthocephalus cadamba Roxb.) from Bogor, West Java. Sampling was carried out at the Dramaga Permanent Nursery, IPB Dramaga Campus, Bogor. Pathogenic fungi were isolated from the part of the leaf that had symptoms of spots or blight and then tested for their pathogenicity against the leaves of white Jabon seedlings using the Koch Postulate method. The results of observations of symptoms on white Jabon leaves were obtained for four types of spot symptoms and two types of blight symptoms. The results of the isolation and identification of pathogenic fungi showed that four genera of fungi caused spot symptoms, namely Botrytis sp., Pestalotiopsis sp., Curvularia sp., and Colletotrichum sp.2, and two genera of fungi caused blight symptoms, namely Curvularia sp., and Colletotrichum sp.1. The Koch Postulate test showed that the six types of fungi isolated caused the leaves of white Jabon seedlings to become necrotic.